An appraisal of the portrayal of child and woman abuse with special references to selected Northern Sotho novels - Mashao, Salome Raisibe (My University, 2004)
Refer to the document
Thesis (M. A. (African Languages)) -- University of the North, 2004
Keywords: Women abuse; Women in literature; Child abuse; Women -- Abuse of -- Africa; Abused women in literature; Psychologically abused women